FORMALIZATION OF SEARCH CONTEXT ON BASE OF ONTOLOGIES AND MULTILINGUISTIC THESAURUSES - Gladun, Anatoly; Rogushina, Julia (International Journal of Computing, 2014)
For more relevant informational retrieval and matching of user request with metadata about informational recourses it is necessary to formulize the user knowledge about subject domain of search. We propose to use the ontologies and associated with them thesauri of the appropriate subject domains for representation of domain knowledge. The algorithms of formation and normalization of the multilinguistic thesauruses, and also methods of their comparison are given in this work.